The archives of a fourteenth century merchant and banker: Francesco Di Marco Datini, of Prato - F. MELIS (PSL Quarterly Review, 2014)
The discovery of the archives of Francesco di Marco Datini of Prato - a 14th century Merchant and Banker of international standing - dates back to 1870. The archives, perhaps the largest and most complete collection of mercantile documents of the Middle Ages, gave rise to research work that culminated in 1928 with an important work by Enrico Bensa, which afforded a general view of the Merchant of Prato himself and of the multifarious activities of his Companies. Today, two initiatives are being carried out for utilising the Datini Archives and making them more widely known. First is the publication of the documents edited along modern lines, in a collection of 30 volumes that will facilitate their consultation and use. Second is a special exhibition of the Archives now being arranged at Prato, which will call the attention of the public to the importance and interest of this cultural patrimony. The present article gives account of both of these undertakings, framed in a brief comprehensive account of Datini himself, showing the significance of his papers and of the studies devoted to them.